Modern Methods of Teaching English in Higher Education Institutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the study of modern trends in the methodology of teaching a foreign language and their influence on the formation and development of the student’s personality. The article discusses the principle of active communication, the principle of individualization in a communicative method, the principle of personality-oriented thinking in an intensive method, through which the final goal is achieved: to teach students not only to participate in communication in a foreign language, but also to introduce them to a foreign language culture.